Role of capsaicin-sensitive C-fiber afferents in neuropathic pain-induced synaptic potentiation in the nociceptive amygdala - Nakao Ayano; Takahashi Yukari; Nagase Masashi; Ikeda Ryo; Kato Fusao (Molecular Pain, 2012)
Abstract Background Neurons in the capsular part of the central nucleus of the amygdala (CeC), a region also called "nociceptive amygdala," receive nociceptive information from the dorsal horn via afferent pathways relayed from the lateral parabrachial nucleus (LPB). As the central amygdala is known to be involved in the acquisition and expression of emotion, this pathway is thought to play central roles in the generation of affective responses to nociceptive inputs. Excitatory synaptic transmission between afferents arising from the LPB and these CeC neurons is potentiated in arthritic, visceral, neuropathic, inflammatory and muscle pain models. In neuropathic pain models following spinal nerve ligation (SNL), in which we previously showed a robust LPB-CeC potentiation, the principal behavioral symptom is tactile allodynia triggered by non-C-fiber low-threshold mechanoreceptor afferents. Conversely, recent anatomical studies have revealed that most of the spinal neurons projecting to the LPB receive C-fiber afferent inputs. Here, we examined the hypothesis that these C-fiber-mediated inputs are necessary for the full establishment of robust synaptic potentiation of LPB-CeC transmission in the rats with neuropathic pain. Results Postnatal capsaicin treatment, which has been shown to denervate the C-fibers expressing transient receptor potential vanilloid type-1 (TRPV1) channels, completely abolished eye-wiping responses to capsaicin eye instillation in rats, but this treatment did not affect mechanical allodynia in the nerve-ligated animals. However, the postnatal capsaicin treatment prevented LPB-CeC synaptic potentiation after SNL, unlike in the vehicle-treated rats, primarily due to the decreased incidence of potentiated transmission by elimination of TRPV1-expressing C-fiber afferents. Conclusions C-fiber-mediated afferents in the nerve-ligated animals may be a required facilitator of the establishment of nerve injury-evoked synaptic potentiation in the CeC. These inputs might play essential roles in the chronic pain-induced plastic changes in the central network linking nociception and negative emotion.